Nandrolone decanoate and resistance exercise affect prostate morphology and hormone receptor interface in adult rats with implications for the aging process - Gomes, F. de C. [UNESP]; Chuffa, L. G. de A. [UNESP]; Fávaro, W. J.; Scarano, W. R. [UNESP]; de Melo-Neto, J. S.; Pinheiro, P. F.F. [UNESP]; Domeniconi, R. F. [UNESP] (Wiley, 2019)
Background: Nandrolone decanoate (ND) is an anabolic–androgenic steroid, and its indiscriminate use leads to subclinical alterations in the hypothalamic–pituitary–gonadal axis and androgen-dependent organs. Objectives: To evaluate the effects of ND, either alone or in combination with resistance exercise (RE), on the levels of sex hormones, converting enzymes, and steroid receptors and the morphology of the ventral prostate (VP) in adult and aged rats. Methods: Forty Sprague–Dawley adult and aged rats were divided into four groups each, sedentary and trained with and without ND. The groups received treatments over 8 weeks. Adult animals were sacrificed immediately following treatment completion, while the aged groups were left untreated until 300 days of age. Results: Adult and aged animals showed reductions in testosterone levels following the different treatments, and 17β-estradiol levels were decreased in the ND-treated groups. The level of 5α-reductase type 2 (5αR2) and aromatase was increased significantly in the prostates of adult animals that performed RE. However, aromatase levels were decreased in the prostates of aged animals that performed RE and were treated with ND, while 5αR2 levels were reduced in aged animals that performed RE without ND treatment. When sex receptors levels were examined, the aged and trained animals presented low androgen receptor (AR) levels. Estrogen receptors (ERs) levels were increased in the prostates of adult animals that received ND. ERβ levels were reduced after treatments in aged animals. The heights of the prostatic epithelium were reduced in all adult treated animals, coinciding with increases in PCNA and PAR4 levels. Discussion: ND and RE alter the levels of hormone, converting enzymes, and sex steroid receptors and the morphology of the VP. These effects were observed in both adult and aged rats. Conclusion: ND, either with or without RE, during post-puberty stage is able to interfere with the morphophysiology of the prostate.
Keywords: apoptosis; hormones; proliferation; resistance exercise training; sex steroid; ventral prostate